The perceptions of future teachers about mathematical modeling and the links with D'Ambrosio's conception and mathematical knowledge for teaching - Claudia de Oliveira Lozada; Felipe Miranda Mota; Sidney Leandro da Silva Viana (Universidade Estadual de Alagoas, 2023)
In this work, we present partial results of a qualitative research that aims to investigate mathematical knowledge for the teaching and practice of mathematical modeling in Basic Education. For that, a data collection was carried out with a group of students of the Degree in Mathematics of the Federal University of Alagoas. The results showed that the researched group showed signs that subdomains of mathematical knowledge for teaching are emerging in initial training, but the perceptions about D'Ambrosio's conception of Modeling and the sociocritical perspective are still fluid, little structured, due to the little contact with the theoretical foundation and practice of Mathematical Modeling in the context of Mathematics Education, making it necessary that in the Mathematics Degree course, mathematical modeling becomes a frequent practice in a specific discipline or inserted in the different disciplines of the Mathematics area so future teachers will be prepared to apply it in their classes.